Infantile systemic hyalinosis: report of a case from Bahrain and review of literature - Zahra Alsahlawi; Fatema Naser Alfayez; Sayed Mohamed Hasan; Deena Mohammed; Emtethal Aljishi (Journal of Biochemical and Clinical Genetics, 2020)
Background: Infantile systemic hyalinosis (ISH), an allelic form of hyaline fibromatosis syndrome, is a rare fatal autosomal recessive disorder that is caused by mutations in the CMG2/ANTRX2 gene encoding the transmembrane anthrax toxin receptor 2. It has a compound of features due to the accumulation of hyaline material in multiple organs including characteristic skin lesions, joint contractures, persistent diarrhea, and failure to thrive. The resulting severe malnutrition can be the cause of death in early infancy. Due to its rarity and early high fatality rate, timely diagnosis is difficult, and children with ISH may die undiagnosed. Case Presentation: In this report, we describe a 3-year-old female diagnosed with ISH after reviewing her clinical and laboratory workup in Salmaniya Medical Hospital. She was diagnosed with ISH based on the clinical presentation of severe skin lesions, painful joint contractures, and later developed renal tubular acidosis. Her diagnosis was confirmed with skin histopathology and identification of homozygous ANTRX2 mutation, c.652T>C, p.Cys218Arg, and Chr4 (GRCh37): g.80957171A>G. Conclusion: While the clinical outcome of the disease is poor without curative treatment, establishing an early diagnosis of ISH, beginning with clinical suspicion to molecular analysis, is important for accurate management as well as carrier and risk assessment of family members. [JBCGenetics 2020; 3(2.000): 108-112]